Development of an Environmental Insurance Program based on Islamic Values in the Palm Oil Industry in Indonesia for Community Welfare - Arif Darmawan; Dwi Ahmadi (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
Economic development is synonymous with growth rates where the relationship between development and environmental sustainability is very clear. Indonesia is blessed by Allah SWT with abundant natural resources. One of Indonesia's potentials is palm oil or CPO (Crude Palm Oil). The CPO industry is one of the biggest contributors to Indonesia's foreign exchange. Palm oil can contribute around 13.50 % to non-oil and gas exports and about 3.50% to Indonesia's Gross Domestic Product (GDP). Until the end of 2020, the export value of CPO in Indonesia reached 27,326.1 tons from various destination countries. However, in the midst of this perspective industrial climate, environmental issues surrounding the CPO industry continue to be voiced from various circles. As a result of such a large demand, it has an impact on land clearing for oil palm production. Real action from the government and palm oil companies is urgently needed to overcome this. Synergy is needed between the government through its policies and the role of oil palm companies through production mechanisms and programs that support the environment, such as the implementation of environmental insurance programs. The environmental insurance program has two insurance policy applications, namely, Polluter Pay Principle and Instrument Cess. However, this environmental insurance program has not been implemented with the right system. Therefore, the actualization of Islamic values is expected to help optimize the program.